Unequal Appropriation of Urban Vegetation in Argentine Cities - Spescha, Veronica (2020)
Seventy-five percent of the human population will live in urban areas by 2050, and urban vegetation will be the main source of ecosystem services. Unequal access to urban vegetation might exacerbate existing socioeconomic differences. Studies performed in cities of developed countries show that the population with higher socioeconomic status has more access to ecosystem services provided by vegetation. In urban areas, with small internal climatic variation, plant productivity measured through satellite imagery is a good indicator of vegetation availability that can be mapped. In this study, we characterized the distribution of plant productivity in 40 Argentine urban centers and we identified socio-environmental variables that control its spatial patterns within and among urban centers. We used socioeconomic indicators obtained from the 2010 National Population and Households Census and a 4-year mean plant productivity measured through the integration of NDVI values derived from MODIS satellite images. In most of the analyzed cities, plant productivity increased as socioeconomic status decreased; and only in 25% of the cities, we found a positive relationship between socioeconomic status and plant productivity. In the latter case, most of the cities were placed in arid environments, where both the cost of watering and the effect of subsidized water on plant productivity are proportionally higher. Buenos Aires and Bariloche, which also showed positive associations between socioeconomic status and plant productivity, are located in humid environments, but Buenos Aires is the most densely populated city of Argentina and Bariloche is a touristic city; in these cities, the relative cost of keeping green spaces instead of building housing infrastructure is also high. These results show that vegetation distribution among socioeconomic status is more diverse than suggested by the literature and that the appropriation of vegetation productivity by groups with higher socioeconomic status only occurs when vegetation cost increases to the point of becoming a luxury good.